Analisis Kandungan Kadar Paracetamol pada Jamu Pegal Linu Menggunakan Spektrofotometri UV VIS - Haryanto Haryanto; Sitti Nur Atika Ningsih; Nabila Syahrani Anwar; Farda Nur Annisa; Meilinda Putri Anastasya; Muh Abdiyal; Ispa Novianti Nanrang; Adinda Safira; Ratu Raisyah Rahmatia Rumbara; Liska Nur (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Jamu is a traditional health drink that has survived in society until now. One of the traditional health drinks that is still ethnic until now is jamu. Jamu has taken root and become the foundation of the strength of the existence of Indonesian culture since ancient times. The purpose of this experiment is to understand the theory of Spectrophotometry, analyze the levels of samples, know the principles of the tools used, and be able to explain the application of spectrophotometry analysis in the pharmaceutical field. This study was conducted using the uv-visible spectrophotometry method using a sample of bone flu herbal medicine that wanted to know the level of paracetamol in the sample. The results obtained from the analysis of the paracetamol content in the bone flu gout herbal medicine showed that the herbal medicine was indicated to contain BKO paracetamol. The levels obtained from the three replications were 0.004%, 0.0016%, and 0.0014% with an average of 0.0010%, so, the paracetamol content in the bone flu herbal medicine sample was 0.0010%. According to BPOM (2006) BKO that is often added to herbal medicine is one of them is paracetamol. This is proven through our observations which show the presence of paracetamol content of 0.0010% in herbal medicine for gout and bone flu.